Checklist of Flowering Plants (Magnoliophyta) of Mount Nglanggeran, Gunungkidul: Confirmation and Update of Flora of Java and APG III - Widodo Widodo; Muhammad Jafar Luthfi (Biology, Medicine, & Natural Product Chemistry, 2017)
This study aimed to collect data on the species plants in Mount Nglanggeran, to confirm and update the existence of these plants from Flora of Java book by Backer & Bakhuizen, and to showing the visual data of plant species in Nglanggeran Mountain. This research used survey method through in-situ visit and specimen collection. Monitoring and visits were conducted based on prediction of flowering period and fruit-bearing season. Eighty plant families of flowering plants were found in the mount Nglanggeran. Based on the phylogenetic arrangement of flowering plants it was found that all the main groups (clades) of flowering plants were found at this location.